A Prospective Open-Label Study for Treatment of Infraorbital Hollows Using a Volumizing Hyaluronic Acid Filler - Smith, Scott W.; Massey, Blaine L.; Hall, Michael B.; Buckingham, Edward D. (Facial Plastic Surgery, 2023)
This study aimed to prospectively evaluate the effectiveness, patient satisfaction, and early adverse events of using the hyaluronic acid filler VYC-20L for the treatment of infraorbital hollowing. A total of 21 participants underwent injection of VYC-20L. FACE-Q satisfaction surveys before and after treatment along with early adverse events surveys were conducted. Pre- and posttreatment photos were graded, and the Allergan Infraorbital Hollows Scale was used to assess the difference in infraorbital hollowing. The results showed infraorbital hollowing improvement with VYC-20L was significant (p < 0.001). FACE-Q Satisfaction with Eyes scores on average were 27 points higher after treatment (p < 0.001). The mean FACE-Q Satisfaction with Decision score was 74.1%. The most common short-term adverse symptoms were tenderness (67%), swelling (62%), and bruising (52%). This study concludes that VYC-20L is an effective nonsurgical treatment option for infraorbital hollowing with high patient satisfaction.
Keywords: infraorbital hollows; hyaluronic acid; filler; VYC-20L